Strong correlation between large gender pay gaps and non-linear pay in certain occupations - Aline Zucco (DIW Weekly Report, 2019)
The gender pay gap of 21 percent in Germany is partly due to the fact that men and women work in different occupations. However, considerable pay gaps between men and women can also be observed within occupations, although the gap is not constant across occupations. In particular, there is a substantial gender pay gap in occupations with non-linear earnings, i.e. earnings increase non-linearly with the number of hours worked. Additionally, occupations which have a high share of leadership positions exhibit a larger gender pay gap. Occupations at public companies tend to have smaller pay gaps. Changes in the organization of work that allow more flexible working hours and top-sharing (dividing a management position into two part-time positions) could help reducing the gender pay gap. Moreover, collective agreements, which usually apply to public sector employers, could also lead to a reduction in the pay gap.
Keywords: J16; J31; J33; J22; J24; 330; Gender Pay Gap; wage distribution; Part Time Gap; occupations